Answer:
a dilation with a scale factor greater than 1 and then a translation (the last option)
Answer:
a). Mileage for carA=
, and mileage for carB=![\frac{ 3x+2}{x(x+1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%203x%2B2%7D%7Bx%28x%2B1%29%7D)
b).total mileage for both is similar to average of them= ![\frac{(mileageA + mileageB)}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%28mileageA%20%2B%20mileageB%29%7D%7B2%7D)
=![\frac{5x+4}{2x(x+1)}[tex]mil/gal](https://tex.z-dn.net/?f=%5Cfrac%7B5x%2B4%7D%7B2x%28x%2B1%29%7D%5Btex%5Dmil%2Fgal)
Step-by-step explanation:
It is given that the distance traveled by car ![A=2x+2=2(x+1)](https://tex.z-dn.net/?f=A%3D2x%2B2%3D2%28x%2B1%29)
And distance traveled by car ![B= 3x+2](https://tex.z-dn.net/?f=B%3D%203x%2B2)
We know the mileage is mile/gallon,
a).So mileage of car
![=\frac{2x+2}{x^2 +x}\\ =\frac{2(x+1)}{x(x+1)} \\=\frac{2}{x}mil/gal](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x%2B2%7D%7Bx%5E2%20%2Bx%7D%5C%5C%20%3D%5Cfrac%7B2%28x%2B1%29%7D%7Bx%28x%2B1%29%7D%20%5C%5C%3D%5Cfrac%7B2%7D%7Bx%7Dmil%2Fgal)
Similarly , the mileage for car
![=\frac{3x+2}{x^2+x} \\=\frac{3x+2}{x(x+1)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B3x%2B2%7D%7Bx%5E2%2Bx%7D%20%5C%5C%3D%5Cfrac%7B3x%2B2%7D%7Bx%28x%2B1%29%7D)
![mil/gal](https://tex.z-dn.net/?f=mil%2Fgal)
b).total mileage for both is similar to average of them= ![\frac{(mileageA + mileageB)}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%28mileageA%20%2B%20mileageB%29%7D%7B2%7D)
![=\frac{2x+2}{x(x+1)}+\frac{3x+2}{x(x+1)}\\ =\frac{2x+2+3x+2}{x(x+1)}\\=\frac{5x+4}{x(x+1)}mil/gal](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x%2B2%7D%7Bx%28x%2B1%29%7D%2B%5Cfrac%7B3x%2B2%7D%7Bx%28x%2B1%29%7D%5C%5C%20%3D%5Cfrac%7B2x%2B2%2B3x%2B2%7D%7Bx%28x%2B1%29%7D%5C%5C%3D%5Cfrac%7B5x%2B4%7D%7Bx%28x%2B1%29%7Dmil%2Fgal)
Now divide by 2 for total(average) mileage.
.
Thus those are the answers.
You multiply 12x8.3 and get the answer 100
<u>Answer:</u>
A red marble out of the same jar, without replacing the first marble.
<u>Step-by-step explanation:</u>
Dependent events are those which involve a first event which affects the outcome of the second event.
This means that the probability of the second event changes because of the occurrence of the first event.
So if a blue marble is drawn out of one jar, then drawing a red marble out of the same jar, without replacing the first marble would be an example of dependent events.